Investigating Metacognitive Strategies in Listening Comprehension among English Language Learners: A Study of University Students in Medan - Sihite, Meida Rabia; Amin, Teguh Satria; Ekayati, Rini; Manihuruk, Leonita Maria Efipanias; Siregar, Masitowarni; Rahmad Husein; Sinar, T. Silvana (International Journal of Educational Research Excellence (IJERE), 2024)
This study investigates metacognitive strategies employed by English language learners (ELLs) during listening comprehension activities. The objectives were to identify the metacognitive strategies commonly employed by English language learners during listening comprehension activities and to examine their awareness of the importance of metacognitive strategies in improving listening skills. Employing a mixed-methods approach, the study collected data through questionnaires and interviews from university students in Medan, Indonesia. This method provided a comprehensive understanding of the strategies used by learners and their perceptions of the strategies' effectiveness. The results reveal that ELLs actively engage in metacognitive strategies, specifically planning, monitoring, and evaluating, to enhance their listening comprehension. The quantitative data from the questionnaires and qualitative insights from the interviews indicate a high level of awareness among students regarding the importance of these strategies. Ethical measures were strictly observed to ensure participant anonymity. This study contributes to the field of language education by highlighting the critical role of metacognitive strategies in listening comprehension and providing empirical evidence of their use among ELLs.